Queer People Who Enter 'Straight' Marriages: The Academic Community's Struggle to Understand an Anomalous Choice. Issue 3 (2nd July 2016) - Benack, Suzanne; Swan, Thomas
ABSTRACT: Since the early 1970s, the academic community has shown a good deal of interest in the motives of people who are sexually and romantically attracted to persons of their own gender but marry other-gendered partners. Despite more than 60 scholarly papers on the question over the past four decades, however, the current academic conversation has moved little since the early 1970s. The authors analyzed 66 scholarly works published between 1969 and 2012 that discussed gay- and bi-identified people's reasons for entering mixed-orientation marriages (marriage between a man and a woman, when one does and the other does not identify as heterosexual). Although the empirical literature consistently supports the importance of love for the other-gendered spouse, most authors have minimized this motive and emphasized the importance of negative motives related to the costs of being identified as gay (e.g., to hide, deny, or cure one's nonstraight sexual orientation). The authors argue that this distortion of the data stems from scholars' unquestioned assumption of dominant cultural scripts regarding desire, love, and marriage. An essentialist understanding of sexual orientation, joined with a romantic view of marriage and a dyadic/monogamist view of romantic love, have rendered the frequently reported love of the queer spouse for the other-sexed partner problematical and 'anomalous.' The authors examine some of the strategies that have been used to minimize discrepant data and suggest alternate strategies to facilitate open academic inquiry into sexual phenomena that are 'anomalous' from the perspective of dominant cultural paradigms.